A design and development approach to Researching Online Arabic Vocabulary Games Learning in IIUM - Sahrir, Muhammad Sabri; Alias, Nor Aziah (Elsevier, 2012)

(untitled)
This paper describes the design and development process of an online Arabic vocabulary games learning prototype for elementary learners at the Centre for Foundation Studies (CFS), International Islamic University Malaysia (IIUM). The effort to produce this learning prototype is an attempt to integrate game-based learning in an online environment, to provide new learning experience for learners who have been through a traditional Arabic teaching and learning methods, and to collect and analyze their feedbacks and responses as the formative evaluation of the prototype. The exploration of the game-based learning prototype potential for use in teaching and learning in real setting by learners and teachers is also among the steps taken to evaluate the practicality of the prototype.